Summer seed mortality of the Pacific oyster, Crassostrea gigas Thunberg grown in Tomales Bay, California, USA : the influence of oyster stock, planting time, pathogens, and environmental stressors - Burge, Colleen; Judah, Linda; Conquest, Loveday; Griffin, Frederick; Cheney, Daniel; Suhrbier, Andrew; Vadopalas, Brent; Olin, Paul G.; Renault, Tristan; Friedman, Carolyn S. (The National Shellfisheries Association, 2007)
Summer seed mortality (SSM) has occurred yearly in Tomales Bay, California since 1993. SSM has resulted in up to 90% cumulative losses, and has been associated with extreme temperature, phytoplankton blooms, and an oyster herpesvirus. In this study, three stocks of Pacific oysters were planted at three sites in California (Inner Tomales Bay, Outer Tomales Bay, and Bodega Harbor) in October of 2000 (Fall) and April of 2001 (Spring) and monitored for mortality, growth, and health status. In April of 2001, a similar study was conducted in Totten Inlet, WA state using cohorts of oysters planted in California; animals were monitored for mortality and growth. Temperature data were collected at all sites; phytoplankton abundance data were collected at the California sites. Mortality occurred only at the Inner Tomales Bay site where losses were correlated with maximum temperatures (r = 0.949) and preferentially affected faster growing oysters (r = 0.916). Significant differences in cumulative mortality were identified among oysters stocks and two of the three oysters stocks planted in the fall outperformed their cohorts planted in the spring (P < 0.0001). Microscopic changes in connective tissue and digestive tubules are consistent with previous observations of herpesvirus infections in oysters including: diffuse to multifocal pertibular hemocyte infiltration, diapedesis, dilation of the digestive tubules, nuclear hypertrophy, and chromatin margination. Nuclear hypertrophy and chromatin margination, in particular, are suggestive of herpesvirus infections; these histological changes were rare indicating the need to use multiple diagnostic methods when oyster herpesviruses are suspected to cause SSM. Temperature maxima (~25°C) experienced at the Inner Tomales Bay site are not considered extreme for Pacific oyster survival; the association between oyster herpesviruses and temperature in Tomales Bay, California is discussed.